2005
DOI: 10.1002/eji.200425637
|View full text |Cite
|
Sign up to set email alerts
|

The major T cell epitope on type II collagen is glycosylated in normal cartilage but modified by arthritis in both rats and humans

Abstract: Type II collagen (CII) is a target for autoreactive T cells in both rheumatoid arthritis and the murine model collagen-induced arthritis. The determinant core of CII has been identified as CII260-270, and the alteration of this T cell epitope by posttranslational modifications is known to be critical for development of arthritis in mice. Using CIIspecific T cell hybridomas we have now shown that the immunodominant T cell epitope in the normal (healthy) human and rat joint cartilage is O-glycosylated at the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 28 publications
7
78
0
Order By: Relevance
“…We have shown that the genetic introduction of pNO 2 (21)(22)(23). For example, citrullination and glycosylation are posttranslational modifications reported to be involved in T cell-dependent autoimmune diseases (21)(22)(23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the genetic introduction of pNO 2 (21)(22)(23). For example, citrullination and glycosylation are posttranslational modifications reported to be involved in T cell-dependent autoimmune diseases (21)(22)(23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…We know from studies in CIA that the nature of such endogenous proteins could be quite complex because the T cell recognition in this case is dependent on various forms of glycosylation of type II collagen (40). In addition, this glycosylation is dependent on the status of chondrocytes in the joints that could vary depending on inflammatory conditions (41). In the present experiments, we could show that the T cell-induced inflammatory cascade in the joints is dependent on cytokines such as IFN-␥ and TNF-␣, which are believed to be secreted by T cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown the importance of galactosylation at position K 264 of CII259-273 for the immune recognition [12][13][14][15][16][17] and that CII in the healthy individuals is completely glycosylated at this position [16]. In line with these findings, an additional modification at position Q 267 by deamidation makes the study of the immune response more complex.…”
Section: Discussionmentioning
confidence: 55%
“…It is well established that during aging, inflammation, trauma or other pathologic processes, the frequency of posttranslational modifications, such as glycosylation, glycation, citrullination, oxidation, deamidation/transamidation or phosphorylation, is increased [10,11]. The role of glycosylated immunodominant CII260-270-peptide for development of autoimmune arthritis has been previously described [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation